The Analisis Penerapan Tata Kelola TI menggunakan COBIT 5.0 dan COBIT 2019 - Denny Ganjar Purnama; Rufman Iman Akbar (JSAI (Journal Scientific and Applied Informatics), 2025)
The rapid development of information technology (IT) has affected many sectors, including higher education. Universitas Pembangunan Jaya (UPJ) implemented two versions of COBIT, COBIT 5.0 and COBIT 2019, to improve their IT management. This research aims to compare the effectiveness of the two versions in supporting IT management at UPJ. The research method used is a qualitative approach with a case study involving in-depth interviews, direct observation, and documentation analysis. The data obtained was analyzed using thematic and comparative approaches. The results showed that COBIT 2019 is more flexible, allows customization to the specific conditions of the university, and improves collaboration between departments. Meanwhile, COBIT 5.0 tends to be more rigid and less adaptive to rapid changes. This research concludes that COBIT 2019 is more effective in IT management at UPJ, as it provides greater flexibility in the management of IT resources and response to environmental changes.